Spectrophotometric Determination of Iron(II) and Cobalt(II) by Direct, Derivative, and Simultaneous Methods Using 2-Hydroxy-1-Naphthaldehyde-p-Hydroxybenzoichydrazone. (27th February 2012) - Devi, V. S. Anusuya; Reddy, V. Krishna
Abstract : Optimized and validated spectrophotometric methods have been proposed for the determination of iron and cobalt individually and simultaneously. 2-hydroxy-1-naphthaldehyde-p-hydroxybenzoichydrazone (HNAHBH) reacts with iron(II) and cobalt(II) to form reddish-brown and yellow-coloured [Fe(II)-HNAHBH] and [Co(II)-HNAHBH] complexes, respectively. The maximum absorbance of these complexes was found at 405 nm and 425 nm, respectively. For [Fe(II)-HNAHBH], Beer's law is obeyed over the concentration range of 0.055–1.373 μ g mL −1 with a detection limit of 0.095 μ g mL −1 and molar absorptivity ɛ, 5.6 × 10 4 L mol −1 cm −1 . [Co(II)-HNAHBH] complex obeys Beer's law in 0.118–3.534 μ g mL −1 range with a detection limit of 0.04 μ g mL −1 and molar absorptivity, ɛ of 2.3 × 10 4 L mol −1 cm −1 . Highly sensitive and selective first-, second- and third-order derivative methods are described for the determination of iron and cobalt. A simultaneous second-order derivative spectrophotometric method is proposed for the determination of these metals. All the proposed methods are successfully employed in the analysis of various biological, water, and alloy samples for the determination of iron and cobalt content.